Revising TAM for hedonic location-based social networks: the influence of TAM, perceived enjoyment, innovativeness and extraversion - Bouwman, M.; Kommers, Petrus; Van Deursen, A. (Inderscience Publishers, 2014)
As a hedonic information system, a location-based social network (LBSN) is often seen as a promising innovative mobile service. However, research on LBSNs is still limited. Little is known about the factors influencing the intention to use LBSNs. Our study aims to explain the critical factors underlying the use of an LBSN, by developing a conceptual framework based on the technology acceptance model, the theory of diffusion of innovations and the five-factor model. To examine our proposed research model, we conducted an online survey among users of a Dutch LBSN. Our results demonstrate that perceived usefulness, perceived ease of use, perceived enjoyment and innovativeness predict the intention to use and the actual use of LBSNs, and hedonic information systems in general. We found no effect of extraversion. Our results suggest that developers of LBSNs should especially aim at pleasance and fun. © 2014 Inderscience Enterprises Ltd.